Cardiovascular outcomes in adults with migraine treated with eptinezumab for migraine prevention: pooled data from four randomized, double-blind, placebo-controlled studies - Timothy R. Smith (BMC, 2021)
Abstract Background Patients with migraine have an increased relative risk of cardio- and cerebrovascular events, and some migraine treatments may exacerbate this risk. The primary objective of this analysis was to determine whether the rate of cardiovascular adverse events was higher for patients with migraine treated with the migraine-preventive eptinezumab, compared with patients receiving placebo. Methods Cardiovascular outcomes in patients with migraine were pooled across four clinical trials (phase 1b, phase 2, and two phase 3 trials) for use of eptinezumab as a preventive migraine treatment for up to 1 year. In all studies, treatment-emergent adverse events (TEAEs) that occurred after the first dose of study treatment (eptinezumab 100 mg, 300 mg, 1000 mg, or placebo) and vital signs were recorded through study completion. Results Cardiovascular TEAEs were rare across all four clinical trials, and rates were similar between patients receiving eptinezumab and those receiving placebo. Cardiovascular TEAEs that did occur were mild or moderate in severity; there were no serious adverse events as per FDA definition. Vital signs (systolic blood pressure, diastolic blood pressure, and heart rate) were not meaningfully different across treatment groups over the course of 56 weeks, compared to placebo. Treatment with eptinezumab did not result in significant new or changed cardiovascular medications used concomitantly compared to placebo. Conclusions In this post hoc analysis of four clinical trials for eptinezumab, doses of 100 mg, 300 mg, and 1000 mg (more than 3 times the highest approved dose) were not associated with clinically relevant changes in vital signs or significant changes in concomitant cardiovascular medication usage, and had low incidences of cardiovascular TEAEs, comparable to placebo. Trial registration NCT01772524 (Study 2), 01/21/2013; NCT02275117 (Study 5), 10/27/2014; NCT02559895 (PROMISE-1), 09/25/2017; NCT02974153 (PROMISE-2), 11/28/2016